Restorasi Embung Sebagai Ekowisata dan Inovasi Olahan Anti Covid-19 â€œBiluluheâ€ Sebagai Upaya Memulihkan Stabilitas Ekonomi Desa - Yantu, Irwan; Bokingo, Agus Hakri (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2020)
This activity aims to (1) educate the community regarding the potential of the village that is owned and can be used as a source of income in encouraging the community's economy, (2) Developing the potential of an embung to become an ecotourism location, (3) Providing training on innovative processing of cassava and freshwater fish to be utilized a traditional anti-Covid-19 "Biluluhe" snack. The activity was carried out for 45 days by involving the community in Hutada'a Village and Buhu Village, Telaga Jaya District, Gorontalo District, Gorontalo Province. The output of this activity is the embung ecotourism location and Biluluhe food products.